Influencia de la Melaza de Caña de Azúcar en la permeabilidad de muestra de suelo arenoso de una subrasante - Condo Barreros, Irvin Andres (2023)
The disrepair of the roads that connect rural communities due to poor soil subgrade treatment, soil type, traffic, among other factors, and the search for new methods to improve the permeability of especially sandy soils, led to work on this research to evaluate the variation of the permeability of sandy soils with the addition of 4%, 8%, 12% and 16% of Sugar Cane Molasses (MCA). In order to achieve the goal, permeability tests were performed on samples of a sandy soil subgrade, using a constant head permeameter. In this way, it was demonstrated that the permeability of sandy soils tends to decrease by incorporating sugar cane molasses, since a percentage of 4% a significant reduction of 18,200% was got, while the highest percentage of molasses used in this research (16%), a reduction of 80.552% was obtained, thus demonstrating that sugarcane molasses can be used as a waterproofing for this type of soil.